Context Specificity of the ANS Stress Response during Two Regrouping Experiments in Goats - Patt, Antonia; Gygax, Lorenz; Wechsler, Beat; Hillmann, Edna; Langbein, Jan; Keil, Nina M. (Frontiers in Veterinary Science, 2016)
The aim of the present study was to analyze whether the activity of the autonomic nervous system (ANS) differs between two regrouping procedures in goats, which would indicate stimulus specificity of these stressors. Applying two regrouping procedures, we evaluated heart rate and heart rate variability (RMSSD, SDNN, RMSSD/SDNN). The two regrouping procedures were 1) introduction of individual goats into established groups (“introduction experiment”) and 2) temporary separation and subsequent reintegration of individuals from/into their group with two levels of contact during separation (“separation experiment”). In the “introduction experiment”, the heart rate of introduced goats while lying decreased continuously from an average 78 beats/minute to 68 beats/minute from before the introduction to the last day of the introduction period. Inversely, RMSSD increased continuously from 41 ms to 62 ms, which, on its own, would indicate an adaptation to the situation. During the “separation experiment”, heart rate while lying was higher when goats were separated in the “acoustic contact treatment” (82 beats/minute on average) compared with the “restricted physical contact treatment” (75 beats/minute on average). This difference reflected a higher level of arousal during the “acoustic contact treatment”. However, heart rate activity did not allow detecting effects of separation or reintegration. Even though it can be assumed that both the separation and introduction of goats are stressful for goats, the ANS reactions observed in the present study differed between the two management procedures indicating that the ANS activation was specific to each situation. In addition, we discuss the ANS results in context with earlier findings of variables of the HPA-axis (fecal cortisol metabolites) and behavior (lying and feeding). As correspondence between ANS, HPA, and behavioral reactions was limited both within and across experiments, the results of the present study underline the concept that stress response patterns are context-specific.